La philosophie espagnole des années 1900-1930, une philosophie poétique ? - Camille Lacau St Guily (Cahiers de Civilisation Espagnole Contemporaine)
Even though it had never been recognized as such, a philosophical tradition did exist in Spain in the 1900-1930's, but was represented by men who were not perceived as philosophers. This article points out that Spain has known a strong philosophical tradition provided we open the universal philosophical Republic to the hybrid profile of « poet-philosophers ». In the 1900-1930's, the Spanish philosophy was a poetic philosophy, a poetic anthropology, driven by, among others, men such as Miguel de Unamuno, but also Gabriel Alomar, Victoriano García Martí, María Zambrano, Federico García Lorca.